Micro RNA based MSC EV engineering: Targeting the BMP2 cascade for bone repair - Huang, Chun-Chieh; Kang, Miya; Leung, Kasey; Lu, Yu; Shirazi, Sajjad; Gajendrareddy, Praveen; Ravindran, Sriram (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stem cell derived extracellular vesicles (MSC EVs) possess excellent immunomodulatory and therapeutic properties. While beneficial, from a translational perspective, extracellular vesicles with consistent functionality and target specificity are required to achieve the goals of precision medicine and tissue engineering. Prior research has identified that the miRNA composition of mesenchymal stem cell derived extracellular vesicles contributes significantly towards extracellular vesicles functionality. In this study, we hypothesized that mesenchymal stem cell derived extracellular vesicle functionality can be rendered pathway-specific using a miRNA-based extracellular vesicles engineering approach. To test this hypothesis, we utilized bone repair as a model system and the BMP2 signaling cascade as the targeted pathway. We engineered mesenchymal stem cell extracellular vesicles to possess increased levels of miR-424, a potentiator of the BMP2 signaling cascade. We evaluated the physical and functional characteristics of these extracellular vesicles and their enhanced ability to trigger the osteogenic differentiation of naïve mesenchymal stem cell in vitro and facilitate bone repair in vivo. Results indicated that the engineered extracellular vesicles retained their extracellular vesicles characteristics and endocytic functionality and demonstrated enhanced osteoinductive function by activating SMAD1/5/8 phosphorylation and mesenchymal stem cell differentiation in vitro and enhanced bone repair in vivo. Furthermore, the inherent immunomodulatory properties of the mesenchymal stem cell derived extracellular vesicles remained unaltered. These results serve as a proof-of-concept for miRNA-based extracellular vesicles engineering approaches for regenerative medicine applications.